2014
DOI: 10.1037/a0037491
|View full text |Cite
|
Sign up to set email alerts
|

The development of time-based prospective memory in childhood: The role of working memory updating.

Abstract: This large-scale study examined the development of time-based prospective memory (PM) across childhood and the roles that working memory updating and time monitoring play in driving age effects in PM performance. One hundred and ninety-seven children aged 5 to 14 years completed a time-based PM task where working memory updating load was manipulated within individuals using a dual task design. Results revealed age-related increases in PM performance across childhood. Working memory updating load had a negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
64
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 43 publications
6
64
2
2
Order By: Relevance
“…Additionally, the absence of any interaction between the participants' age and their level of expertise with the procedural task seems to confirm that, although it affects PM performance, the cognitive demand associated with the ongoing activity does not totally account for the improvement observed in time-based memory abilities with age. Moreover, stepwise regression analyses also revealed the expected positive relation between the score for strategic time monitoring and PM performance in both experimental groups (expert and novice), indicating that the use of an appropriate strategy seems to improve children's PM performance even when their resources are engaged in a cognitively demanding ongoing task (Costa et al, 2010;Mäntylä et al, 2007;Voigt et al, 2011;Voigt et al, 2014;Zinke et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Additionally, the absence of any interaction between the participants' age and their level of expertise with the procedural task seems to confirm that, although it affects PM performance, the cognitive demand associated with the ongoing activity does not totally account for the improvement observed in time-based memory abilities with age. Moreover, stepwise regression analyses also revealed the expected positive relation between the score for strategic time monitoring and PM performance in both experimental groups (expert and novice), indicating that the use of an appropriate strategy seems to improve children's PM performance even when their resources are engaged in a cognitively demanding ongoing task (Costa et al, 2010;Mäntylä et al, 2007;Voigt et al, 2011;Voigt et al, 2014;Zinke et al, 2010).…”
Section: Discussionmentioning
confidence: 85%
“…In this context, like adults' performance (e.g., Schnitzspahn, Stahl, Zeintl, Kaller, & Kliegel, 2013), children's PM performance is usually shown to be related to the difficulty of the ongoing task as Running head: Metamemory Knowledge and Prospective Memory 5 well as to their level of executive abilities Mackinlay, Kliegel, & Mäntylä, 2009;Mahy, Moses, & Kliegel, 2014;Ward, Shum, McKinlay, Baker, & Wallace, 2007; for a review of the involvement of executive functions in children's PM development, see Mahy, Moses, & Kliegel, in press). In addition, time-based memory performance is also shown to be linked to participants' use of an effective time monitoring strategy (Kretschmer, Voigt, Friedrich, Pfeiffer, & Kliegel, 2013;Mäntylä, Carelli, & Forman, 2007;Voigt, Aberle, Schonfeld, & Kliegel, 2011;Voigt at al., 2014;Zinke et al, 2010). For instance, using an experimental paradigm in which children had to drive a vehicle (ongoing task) and to remember to refuel it before running out of gas (time-based memory task in which the fuel gauge served as an equivalent of the clock), Voigt et al (2011) demonstrated the involvement of strategic time monitoring in enhancing PM performance in children aged between 7 and 9 years old (for similar findings in preschool and early-school-aged children, see Kretschmer et al, 2013).…”
mentioning
confidence: 99%
“…By contrast, reactive control is engaged in the moment to resolve interference when it arises (e.g., improvising during the presentation; ). Young children rely exclusively on reactive control, whereas children 6 years and older engage proactive control in a variety of tasks: tapping response inhibition , set‐shifting , working memory , and prospective memory .…”
Section: An Expanding Control Repertoire For More Flexible Control Enmentioning
confidence: 99%
“…Developmental improvements in PM performance have mainly been attributed to the parallel development of executive functions (e.g., Altgassen, Vetter, Phillips, Akgün, & Kliegel, 2014;Wang et al, 2011), and thus the ongoing development of the prefrontal cortex into young adulthood (Casey, Tottenham, Liston, & Durston, 2005;Luciana, Conklin, Hooper, & Yarger, 2005). In general most research on age differences in PM has examined the role of the person or task characteristics during the phases of intention initiation and execution by manipulating the extent to which executive-control resources are needed Wang et al, 2011) or available to perform the PM task (Mahy et al, 2015;Voigt et al, 2014). In line with the predictions of the multi-process framework and PAM model, these studies report larger age differences in PM tasks requiring more executive control or when fewer executive control resources are available.…”
mentioning
confidence: 99%
“…Despite the consistently-reported poorer PM performance of children and adolescents compared to young adults Voigt et al, 2014), these studies have mainly focused on younger and/or older adults. This lack of research on possible strategies to improve PM in children and adolescents is surprising given that it is considered to be an essential precursor of independent living (Kliegel, Jäger, Altgassen, & Shum, 2008).…”
mentioning
confidence: 99%